Grau de comprometimento e tempo de trânsito orofaríngeo em disfagia no acidente vascular encefálico - Dallaqua, Rarissa Rúbia [UNESP] (2014)
The scales of severity oropharyngeal dysphagia neurogenic, including stroke, prioritize laryngeal penetration and aspiration laryngotracheal as markers. However, oropharyngeal dysphagia in this population have found wide variation in oral and pharyngeal transit times swallowing, and these parameters can also involve, respectively, the nutritional status and safety of the lower airway in post-stroke individuals. The aim of this was to associate the total oral transit time, pharyngeal response and pharyngeal transit time with the severity oropharyngeal dysphagia scale in stroke. Cross-sectional clinical study. The study included 61 subjects after ischemic stroke, independent of the injured hemisphere. The data were recorded one to 30 days after the ictus. Of these, 28 were males and 33 females, with ages ranging from 40 to 101 years (mean 65 years). Videofluoroscopy with specific software developed to measure the time of oral and pharyngeal transit was applied in patients receiving 5 ml of paste bolus. It was measured the total oral transit time (TOTT), response pharyngeal (RPT), and pharyngeal transit (PTT). The subjects were divided into two groups TOTT, RPT PTT and analyzed . The first group ( G1a ) consisted of patients who presented TOTT to 2000 ms and group 1b ( G1b ) individuals who had greater than 2000 ms TOTT . The second group ( G2a ) was composed of individuals who had TRF up to 250 ms and group 2b ( G2b ) subjects who had greater than 250 ms.The 3a ( G3a ) TRF group was composed of individuals who had PTT to 1000 ms and group 3b ( G3b ) subjects who had greater than 1000 ms PTT. At the end of the quantitative analysis was applied of severity oropharyngeal dysphagia proposed by Daniels et al. 1997. The results showed no significant association between total oral transit time, response pharyngeal and pharyngeal transit with severity oropharyngeal dysphagia respectively. When it was analysed between the normal and altered 18...